Autoantibodies against zinc transporter 8 are related to age, metabolic state and HLA DR genotype in children with newly diagnosed type 1 diabetes. Issue 8 (November 2013) - Salonen, K. M.; Ryhänen, S.; Härkönen, T.; Ilonen, J.; Knip, M.; ,
Abstract Background We set out to define the characteristics of humoral autoimmunity against ZnT8 in children and adolescents with newly diagnosed T1D in relation to age and metabolic status at diagnosis, human leucocyte antigen (HLA) genotype and family history of T1D. Methods A total of 2115 subjects <15 years of age were analysed for antibodies against zinc transporter 8, ICA, GADA, IAA, IA‐2A, HLA DR‐DQ genotype, blood pH, plasma glucose and β‐hydroxybutyrate concentrations. Their family history of T1D was also recorded. Results Zinc transporter 8 antibodies (ZnT8A) were detected in 63% of the cases. ZnT8A positivity was associated with older age at diagnosis (mean 8.2 years versus 7.5 years, p < 0.001). Seven subjects (0.3%) had ZnT8A as their single autoantibody. Diabetic ketoacidosis at diagnosis was less common among subjects with ZnT8A than among those without (16% versus 20%, p = 0.012). The prevalence of ZnT8A was decreased in DR3/DR4 heterozygotes when compared with those with other DR combinations (p < 0.001). Subjects with the neutral DR13‐DQB1*0604 haplotype tested more frequently positive for ZnT8A than the rest of the population (p < 0.001). A positive family history of T1D showed no association with ZnT8A prevalence or levels. Conclusions Antibodies for ZnT8 is related to age and metabolic status at diagnosis as well as HLA genotype but does not significantly improve the detection rate of β‐cell autoimmunity in Finnish children and adolescents affected by T1D. Copyright © 2013 John Wiley & Sons, Ltd.